Acute physiological responses and time-motion characteristics of two small-sided training regimes in youth soccer players - Hill-Haas, S. V.; Rowsell, G. J.; Dawson, B. T.; Coutts, A. J. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this study was to examine the acute physiological responses and time-motion characteristics associated with continuous and intermittent small-sided games (SSGs). The continuous (SSGC) regime involved 24 minutes' playing duration (no planned rest intervals), whereas the intermittent regime (SSGI) involved 4 × 6-minute bouts with 1.5 minutes of passive planned rest (work:rest ratio 4:1). Both training regimes were implemented across 3 SSG formats, which included games with 2 vs. 2, 4 vs. 4, and 6 vs. 6 players. Sixteen men's soccer players (mean ± SE: age = 16.2 ± 0.2 years, height = 173.7 ± 2.1 cm, body mass = 65.0 ± 2.5 kg, estimated Vo2max = 54.8 ± 0.7 ml/kg/min) participated in the study. Heart rate (HR) was measured every 5 seconds during all SSGs. Global ratings of perceived exertion (RPEs) were recorded immediately after the SSGs using the Borg scale (RPEs, 6-20). Capillary blood samples were drawn at rest and within 5 minutes after the end of each SSG. Time-motion characteristics were measured using portable global positioning system units. There were no significant differences between SSGC and SSGI for total distance covered or for distance traveled while walking, jogging, or running at moderate speed. However, players covered a significantly greater distance at 13.0-17.9 km/h, a greater total distance at higher running speed, and a greater total number of sprints (>18 km/h) with SSGI compared with SSGC. In contrast, global RPE and %HRmax were significantly higher in SSGC than in SSGI. Both intermittent and continuous SSG training regimes could be used during the season for match-specific aerobic conditioning. However, both training regimes used in this study seem unlikely to provide a sufficient stimulus overload for fully developing Vo2max.